Impact of nanoplastics on hemolymph immune parameters and microbiota composition in Mytilus galloprovincialis. (July 2020) - Auguste, Manon; Lasa, Aide; Balbi, Teresa; Pallavicini, Alberto; Vezzulli, Luigi; Canesi, Laura
Abstract: Ocean contamination by micro- and nanoplastics represents a potential threat to marine biota, from bacterial communities to higher organisms. In this work, the effect of in vivo exposure of Mytilus galloprovincialis to amino modified nanopolystyrene (PS–NH2 ) (10 μg/L, 96 h) on hemolymph immune parameters and microbiota composition were investigated. Nanoplastics significantly affected immune parameters (decreased phagocytosis, increased ROS and lysozyme activity, inhibition of NO production). These changes were associated with a shift in hemolymph microbiota composition, with increase in some genera ( Arcobacter-like, Psychrobium, Vibrio ), and decreases in others ( Shewanella, Mycoplasma ). The results indicate that exposure to nanoplastics can impact on the microbiome of marine bivalves, and suggest that downregulation of immune defences induced by PS-NH2 may favour potentially pathogenic bacteria. These data underline how exposure to nanoplastics may represent a potential threat to the complex interplay between innate immunity and host microbiota, thus affecting the homeostatic processes involved in maintenance of organism health. Graphical abstract: Image 1 Highlights: Nanoplastics-NPs may affect the microbiome of marine organisms. Effects of exposure to amino modified nanopolystyrene on Mytilus hemolymph. NPs induced changes in immune parameters and a shift in microbiome. NPs may alter the interplay innate immunity/bivalve host microbiota. This may favour potential pathogens with possible threat to organism health.